Effect of the Self-monitoring of Calendar Documentation on the Transmission Control and Treatment Outcomes - Purba, Bahtera Bindavid; Aritonang, Evawany Yuanita (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Tuberculosis can cause a substantial challenge to public health, especially in developing countries. The objective of this research is to determine the effect of intervention of SM-CD on the control of TB transmission in one treatment period (6 months) of TB. This Research using the quasi-experimental post-test only with control group design. The analytical unit consisted of 96 TB cases from two primary health centers as the SM-CD and 87 TB cases as the control group from two different primary health centers. The results of analysis after adjustment found that behavior of controlled taking medicine (ARR= 1.44; 95%CI: 1.22-1.70), controlled environment (ARR= 3.59; 95% CI: 2.18-5.90), and controlled droplet nuclei (ARR=4.04; 95%CI: 2.53-6.45) were found to be significantly higher in the SM-CD than the control group. The treatment outcome showed that recovery (ARR=1.95; 95%CI: 1.44-2.65), completeness (ARR= 1.65; 95%CI: 1.32-1.85), undrop out (ARR=1.25; 95%CI: 1.13-1.38), and cases no failed (ARR=1.43; 95%CI:1.24-1.65) was found to be significantly higher in the SM-CD was compared with the control group. The SM-CD intervention was effective in increasing the behavior of TB transmission control, treatment outcomes, and effective as a data collection tool that can be used to improve the surveillance system for TB transmission control.